A Night in Acadie - Chopin, Kate (Saga Egmont, 2022)
Love for unavailable men, regret, unhappy marriages, priests and an old woman losing her memory, these stories cover many issues we still face today. A young woman tired of marriage resolves to leave her husband, making her way to New Orleans alone. Finished with work for the day, Telèsphore decides to take the train into town. A woman content with spinsterhood unexpectedly finds herself responsible for her neighbour\'s four young children. \'A Night in Acadie\' is a collection of short stories by Kate Chopin and a fantastic read for any classics fan.-